Time-course of attentional bias for culture-related cues in Mongolian-Chinese bilingual children. (December 2019) - Yu, Hongyu; Yao, Nisha; Zhang, Jijia; Gao, Bing
Aims and objectives/purpose/research questions: Using a modified dot-probe task, the present research examined the time-course of attentional bias for culture-related cues in Mongolian-Chinese bilinguals. Design/methodology/approach: Using a mixed experimental design, children with different language fluency (fluent bilingual, limited bilingual and mandarin monolingual) were recruited ( N = 168; 51% boys; Mage = 9.88 years, SD = 0.38 years; 59% Mongolian) to complete a dot-probe task in which they were shown pairs of pictures representing Mongolian and Han culture for short (60 ms) and long (500 ms) exposure durations. The difference between fluent and limited bilinguals lies in their proficiency in Mongolian. Data and analysis: The attentional bias scores ( d ) were entered into a 2 × 3 mixed design repeated-measures analysis of variance with language fluency (fluent bilingual versus limited bilingual versus monolingual) as a between-subjects variable and the time-course (60 versus 500 ms) as a within-subject variable. Findings/conclusions: In the task, compared with pictures representing Han culture, all students showed preferential attention to pictures conveying Mongolian culture across presentation durations. However, for 60 ms, fluent bilinguals showed a smaller attentional bias than did monolinguals, with no difference between limited bilinguals and monolinguals; there was no significant difference among the three groups at 500 ms. Originality: Relatively less research has been performed on comparative analysis between fluent and non-fluent bilinguals, and most of the culture-related content is measured by subjective methods. This study attempts to directly compare these two bilinguals' attentional bias for culture-related cues using a dot-probe task. Significance/implications: The results of comparative analysis showed that fluent bilinguals were more familiar with Mongolian language and preserved their ethnic culture better, which may indicate a close relationship between language and culture.